Preparation and Properties of Foaming Agent for Air Foam Flooding - Guo Donghong; Cui Xiaodong; Yang Xiaopeng (International Journal of Petroleum Technology, 2019)
In order to meet the requirements of air foam flooding in Dagang Gangdong Oilfield, two kinds of foaming agents, GFPA-1 and GFPA-2, were prepared by sulfonation, neutralization and high-temperature hydrolysis of α-olefins with different carbon chain lengths in the laboratory. The test results of foaming agents for its properties showed that when the concentration of foaming agent was over 0.5%, the initial foaming volumes of the two foaming agent systems were more than 500mL, and the foam half-life of GFPA-2 was about 3.5 hours, obviously longer than that of GFPA-1. Therefore, GFPA-2 was selected as the foaming agent for air foam flooding. The experimental results of static adsorption, plugging and core displacement performance of GFPA-2 foaming agent showed that the initial foaming volume of GFPA-2 foaming agent could still maintain 500mL after 48 hours of adsorption at a concentration of 0.5%, and when the ratio of gas to liquid was 1: 1, the resistance factor was more than 50. When a 0.4% foaming agent was injected with 0.35 PV slug, the displacement efficiency of air foaming flooding was 17.4% higher than that of water flooding.